(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Information Literacy isthe key competency for the information age. The paper discusses differentdefinitions, need and importance of information literacy to promote the use ofeffective information services. Information literacy is a survival skill in theinformation age irrespective of status and in the society. An attempt has beenmade in this paper to know the awareness of e-resources and e-learningtechnology to learn and adopt new learning methodologies.